Wetgevende initiatieven in de sportsector : Veiligheidsfonds, Sportsponsorfonds : persconferentie 5 juni 1991 - Peeters, Leo; Willockx, Freddy (Brussel: SP, 1991)
"Dhr. F. Willockx en Dhr. L. Peeters ; met medewerking van de SCS"